INTERVENSI KEPERAWATAN UNTUK PENCEGAHAN KEJADIAN PNEUMONIA PADA PASIEN STROKE - Jerau, Emiliani Elsi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Stroke patients are susceptible to respiratory problems and complications in the lungs, namely pneumonia, which most often occurs during stroke treatment. The aims of this study is to review the various literature on interventions that nurses can do to prevent and treat pneumonia in stroke patients. Search methods using electronic databases Science Direct, Scopus, Pubmed, and Google Scholar with a search range of 2017-2022. The inclusion criteria were research conducted on all stroke patients, both ischemic and hemorrhagic, the intervention given was a nursing action, and the outcome assessed was pneumonia. Five articles were reviewed and found several interventions used to prevent and reduce the incidence of pneumonia in stroke patients. Nursing actions that can be done are dysphagia screening and oral care. Conclusion: Dysphagia screening and and oral care can used to prevent and reduce the incidence of pneumonia in stroke patients.